Genetic variability of Pantaneiro horse using RAPD-PCR markers Variabilidade genética do cavalo Pantaneiro utilizando marcadores RAPD-PCR - Andréa Alves do Egito; Beatriz Helena Fuck; Concepta McManus; Samuel Rezende Paiva; Maria do Socorro Maués Albuquerque; Sandra Aparecida Santos; Urbano Gomes Pinto de Abreu; Joaquim Augusto da Silva; Fabiana Tavares Pires de Souza Sereno; Arthur da Silva Mariante (Revista Brasileira de Zootecnia, 2007)
Blood samples were collected from Pantaneiro Horses in five regions of Mato Grosso do Sul and Mato Grosso States. Arabian, Mangalarga Marchador and Thoroughbred were also included to estimate genetic distances and the existing variability among and within these breeds by RAPD-PCR (Random Amplified Polymorphic DNA - Polymerase Chain Reaction) molecular markers. From 146 primers, 13 were chosen for amplification and 44 polymorphic bands were generated. The analysis of molecular variance (AMOVA) indicated that the greatest portion of detected variability was due to differences between individuals within populations (75.47%). Analysis of the genetic variability between pairs of populations presented higher estimates for the five Pantaneiro populations with the Arabian breed, while lowest estimates were presented by pairs formed among the Pantaneiro populations with the Mangalarga Marchador. Highest genic diversity was shown by the Pantaneiro (0.3396), which also showed highest genetic distance with the Arabian and lowest with Mangalarga Marchador breed. UPGMA dendrogram showed distinct differences between naturalized (Pantaneiro and Mangalarga Marchador) and exotic (Arabian and Thoroughbred) breeds. In the dendrogram generated by UPGMA method, the similarity matrix generated by the Jaccard coefficient showed distinction between the naturalised breeds, Pantaneiro and Mangalarga Marchador, and the exotic breeds, Árab and English Thoroughbred. Results suggest that the Pantaneiro presents a higher genetic variability than the other studied breeds and has a close relationship with the Mangalarga Marchador. Amostras de sangue foram coletadas de cavalos Pantaneiros de cinco regiões dos estados de Mato Grosso do Sul e Mato Grosso. As raças Mangalarga Marchador, Árabe e Puro-Sangue Inglês (PSI) usando marcadores moleculares RAPD-PCR (Random Amplified Polymorphic DNA - Polymerase Chain Reaction) foram incluídas no intuito de se calcular as distâncias genéticas e comparar a variabilidade genética entre e dentro de cada uma das raças. Dos 146 primers escrutinados, 13 foram escolhidos para amplificação com cada um dos indivíduos das oito populações, gerando um total de 44 bandas polimórficas. Os resultados encontrados na Análise de Variância Molecular (AMOVA) indicam que grande parte da variabilidade genética detectada se deve a diferenças entre indivíduos dentro de populações (75,47%). Na análise da estimativa dos percentuais de variabilidade genética entre pares de populações, foram observados maiores valores para os pares formados entre as cinco populações de cavalo Pantaneiro e a raça Árabe, enquanto os menores percentuais ocorreram entre Pantaneiro e Mangalarga Marchador. Maior índice de diversidade gênica foi observado na raça Pantaneiro (0,3396). No dendrograma gerado pelo método UPGMA, a partir da matriz de similaridade obtida pelo coeficiente de Jaccard, houve distinção entre as raças naturalizadas (Pantaneiro e Mangalarga Marchador) e as exóticas (Árabe e PSI). Os resultados encontrados sugerem que o Pantaneiro apresenta maior variabilidade genética que os de outras raças e está estreitamente relacionado ao Mangalarga Marchador.